A case series study on the effect of Ebola on facility-based deliveries in rural Liberia. Issue 1 (December 2015) - Lori, Jody; Rominski, Sarah; Perosky, Joseph; Munro, Michelle; Williams, Garfee; Bell, Sue; Nyanplu, Aloysius; Amarah, Patricia; Boyd, Carol
Abstract Background As communities' fears of Ebola virus disease (EVD) in West Africa exacerbate and their trust in healthcare providers diminishes, EVD has the potential to reverse the recent progress made in promoting facility-based delivery. Using retrospective data from a study focused on maternal and newborn health, this analysis examined the influence of EVD on the use of facility-based maternity care in Bong Country, Liberia, which shares a boarder with Sierra Leone - near the epicenter of the outbreak. Methods Using a case series design, retrospective data from logbooks were collected at 12 study sites in one county. These data were then analyzed to determine women's use of facility-based maternity care between January 2012 and October 2014. The primary outcome was the number of facility-based deliveries over time. The first suspected case of EVD in Bong County was reported on June 30, 2014. Heat maps were generated and the number of deliveries was normalized to the average number of deliveries during the full 12 months before the EVD outbreak (March 2013 – February 2014). Results Prior to the EVD outbreak, facility-based deliveries steadily increased in Bong County reaching an all-time high of over 500 per month at study sites in the first half of 2014 – indicating Liberia was making inroads in normalizing institutional maternal healthcare. However, as reports of EVD escalated, facility-based deliveries decreased to a low of 113 in August 2014. Conclusion Ebola virus disease has negatively impacted the use of facility-based maternity services, placing childbearing women at increased risk for morbidity and death.